ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK DI BALI TANGI SPA - Windu Wirajaya, Gede; Wrasiati, Luh Putu; Bayu Sadyasmara, Cokorda Anom (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
This study aims to know about the primary attributes at Bali Tangi Spa to get the customer satisfaction, to know the grade of customer satisfaction on product at Bali Tangi Spa, and to choose which attributes should be the priority to be improved by the company to achieve the customer satisfaction. The study was conducted at Bali Tangi Spa. The sample was 110 respondents used purposive sampling method. The data collected by distributed questionnaires and directly to respondents. This study using the Importance Performance Analysis (IPA) method. The result showed that the highest grade of customer satisfaction was Bali Tangi Spa have many variant of product with the compatibility level of 144,94%. The lowest of grade customer satisfaction was the price of product is relevant with the compatibility level of 84,34%. The attributes that must have priority was the price of product is relevant and the availability of the product that compatible for the customer. Keywords: customer satisfaction, Importance Performance Analysis, Spa, Bali Tangi Spa.
Keywords: 121